(untitled) (Research, Society and Development, 2019)
The Federal Constitution of 1988 brings in its text, Section III, the crimes of responsibility of the President of the Republic, defined in an exemplary way in article 85, items I to VII. Such political-administrative offenses have a rite different from that of ordinary crimes. In this article, the objective was to proceed on the differences between common infractions and responsibility, through a constitutional approach. For that, a method of qualitative research approach was used, with the purpose of interpreting constitutional and infraconstitutional norms, and as bibliographical and documentary research technique. As results, it was observed that different penalty procedures on liability crimes are of great importance to strengthen State Sovereignty, protect the President of the Republic from political judgments and keep the internal administration safeguarded.